Hate crime policy and disability : from vulnerability to ableism - Taylor, Seamus (Book collections on Project MUSE., 2022)
"Outlining the key developments of the Disability Hate Crime policy agenda, Seamus Taylor brings together a unique consideration of the theoretical and practical questions at its heart. This book analyses the contributions of activists, politicians, policymakers and criminal justice system practitioners to policy development, and critiques both the under-recognition of disability prejudice fuelled by ableism and the challenge of vulnerability in addressing disability hostility. Concluding that a critically reflective approach on the part of policymakers and practitioners can lead to progress, the author gives clear policy recommendations to address current challenges in the criminal justice system."--Publisher's description.